Transient Headache and CSF Lymphocytosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
A transient syndrome of migrainous headache with neurologic deficits and CSF lymphocytic pleocytosis is described in 7 young adult patients examined at the Strong Memorial Hospital, University of Rochester Medical Center, Rochester, NY.